Chemoinformatics: Applications of Computer Science in the Analysis of Chemical Structures (on the Example of Cadmium Sulfide) - Maksimov, Anatolii G.; Завалишин, Арсений Дмитриевич; Abramov, Maxim V.; Tulupyev, Alexander L. (Computer Tools in Education, 2019)
The article is aimed at demonstrating the practical application of graph theory as a subsection of the theoretical foundations of computer science in solving one of the interdisciplinary problems — describing the structure of the cadmium sulfide molecule using methods and indices of chemoinformatics. The article presents the results of calculations of the atom-bond connectivity index (ABC), of the geometric and arithmetic index GA, of the generalized Randic index, GA5 and ABC4, of the Zagreb indices for the chemical graph of cadmium sulfide (CdS). Topological indices for cadmium sulfide are considered for the first time, although the task of calculating these indices is not new in itself. The relevance of the results is emphasized by the fact that cadmium sulfide is widely used in various fields, such as optoelectronics, photodetectors, photoresistors, etc.